1584PExploring resistance to nivolumab [NIV] applying an Immune Genomic Signature (IGS) in advanced pretreated NSCLC [PRINCiPe study]. (1st October 2019) - Pilotto, S; Vita, E; Sperduti, I; Noia, V P Di; Grizzi, G; D'Argento, E; Simbolo, M; Vicentini, C; Caliò, A; Mafficini, A; Carbognin, L; Corbo, V; et al.
Abstract: Background: Specific genomic abnormalities in immune-escape/editing-related genes have been demonstrated to be associated with immunotherapy resistance. In the light of this hypothesis, with the final aim to identify a potential predictive signature for immunotherapy, we designed the PRINCiPe (Predictors of Resistance to Immunotherapy with NIV) study in advanced pretreated non-small cell lung cancer (APNSCLC). Methods: FFPE-tumor blocks of APNSCLC pts undergone NIV were retrospectively sequenced for Somatic Mutations/Copy Number Variations (SM/CNV) (Ampliseq 17-genes customized panel: APLNR, B2M, IFNAR1, IFNAR2, IFNGR1, IFNGR2, IRF9, JAK1, JAK2, JAK3, PIAS4, PTPN2, SOCS1, STAT1, STAT2, STAT3, TYK2). Endpoints of the PRINCiPe study were overall-, progression-free-survival (OS/PFS) and objective response rate (ORR). Results: Overall, 44 APNSCLC pts were collected and analysed. Main patients characteristics: median age 69.5 yrs, median number of previous lines 3 (2-5), 2 nd line NIV (75.0%), male/female 77.3/22.7%, squamous/non-squamous 31.8/68.2%, EGFR mutant 5 (11.4%), median follow-up 6.8 months (range 1-23), deaths 24 (54.5%). JAK3/JAK2 (7/3 pts, 15.9/6.8%) CNV and IFNAR2 SM (4 pts, 9.1%) were the most frequent (>1 pts) abnormalities. Those pts (n = 15) harboring JAK3, PIAS4, PTPN2, STAT3, IFNAR2 SM and/or JAK2/3 CNV (IGS+) had a significantly lower PFS than those without (IGS-) (median PFS 2.8 vs. 6.6 months; p = 0.006), while a trend towards significance was observed in terms of OS (median OS 5.1 vs. 13.0 months for IGS+ and IGS-, respectively; p = 0.06 log-rank, p = 0.05 Tarone-Ware). At multivariate analysis, IGS+ was independently associated with a shorter PFS (HR 2.64, 95% CI 1.3-5.4, p = 0.008). IGS+ pts were significantly more probable to be affected by liver metastases than those without (p = 0.01). Conclusions: The identified IGS was able to select APNSCLC pts with a significant lower chance to benefit from NIV, supporting the existence of an intrinsic genomic-detectable resistance. Further analyses are ongoing, including a comprehensive transcriptome analysis. Legal entity responsible for the study: Emilio Bria. Funding: University of Verona. Disclosure: S. Pilotto: Honoraria (self): AstraZeneca, BMS, Roche, MSD, Boeringher Ingelheim; Research grant / Funding (self): AIRC ; Travel / Accommodation / Expenses: BMS, Roche, AstraZeneca, Boeringher Ingelheim. M. Milella: Honoraria (self): Pfizer, EUSA Pharma, AstraZeneca. E. Bria: Honoraria (self): MSD, AstraZeneca, Celgene, Pfizer, Helsinn, Eli Lilly, BMS, Novartis, and Roche; Research grant / Funding (self): AIRC. All other authors have declared no conflicts of interest.